How infants know minds - Reddy, Vasudevi (Harvard University Press, 2008)
"In this book, Vasudevi Reddy draws on the every-day emotional engagements often reported by parents as well as a wide body of recent research in psychology. Using compelling evidence that young babies can tease, joke, pretend, clown, and show off, she shows that the awareness of different aspects of other people's minds - attention and intentions and expectations - develops from an early age." "Reddy deals with the persistent problem of other minds by proposing a "second person" solutions: we know other minds if we can respond to them. And we respond most intensely and richly when we are directly involved with them." "Reddy's emphasis on involvement rather than observation challenges psychology's traditionally detached stance: for adults as well as for infants it is emotional engagement that allows an awareness of minds. A feeling of minds, Reddy argues, is present from the beginning of life. The starting point for psychological awareness is not isolation but emotional relation."--Jacket.